AWE for Formative Purposes in the EFL Context: : A Study of Multiple Revisions in Academic Abstract Writing - Rodríguez-Peñarroja, Manuel (International Journal of English Studies, 2025)
The use of automated writing evaluation (AWE) tools for writing practices has become a central issue in English as a second and foreign language teaching contexts. Researchers appear to agree that students’ positive outcomes hinge upon their integration with formative purposes. Nonetheless, few studies have addressed multiple revisions and automated feedback provision in students’ academic writing development. In this context, an instructional treatment for the integration of this technology has been designed. Explicit instruction on academic writing, AWE workshops, and practice activities remain at its core. Hence, this paper examines the effects of self- and AWE-mediated writing revisions on undergraduate learners’ academic writing performance over time and at different levels of proficiency. A series of repeated-measures analysis of variance (ANOVA) were computed to study participants’ syntactic complexity, readability and language issues, and lexical diversity outcomes. Results revealed improvement in some of the dependent variables, that is, language issues reduction and increased type-token ratio mean scores, which could represent an initial step towards reconsidering the provision of automated written feedback.